Antibubbles enable tunable payload release with low-intensity ultrasound - Moreno Gomez, Nicolas; Athanassiadis, Athanasios G.; Poortinga, Albert T.; Fischer, Peer (Advanced materials, 2023)
The benefits of ultrasound are its ease-of-use and its ability to precisely deliver energy in opaque and complex media. However, most materials responsive to ultrasound show a weak response, requiring the use of high powers, which are associated with undesirable streaming, cavitation, or temperature rise. These effects hinder response control and may even cause damage to the medium where the ultrasound is applied. Moreover, materials that are currently in use rely on all-or-nothing effects, limiting the ability to fine-tune the response of the material on the fly. For these reasons, there is a need for materials that can respond to low intensity ultrasound with programmable responses. Here it is demonstrated that antibubbles are a low-intensity-ultrasound-responsive material system that can controllably release a payload using acoustic pressures in the kilopascal range. Varying their size and composition tunes the release pressure, and the response can be switched between a single release and stepwise release across multiple ultrasound pulses. Observations using confocal and high-speed microscopy reveal different ways that can lead to release. These findings lay the groundwork to design antibubbles that controllably respond to low-intensity ultrasound, opening a wide range of applications ranging from ultrasound-responsive material systems to carriers for targeted delivery.